Z gamma production and limits on anomalous ZZ gamma and Z gamma gamma couplings in pp collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (Elsevier, 2007)
We present a study of eeγ and μμγ events using 1109 (1009) pb-1 of data in the electron (muon) channel, respectively. These data were collected with the DØ detector at the Fermilab Tevatron p over(p, ̄) collider at sqrt(s) = 1.96   TeV. Having observed 453 (515) candidates in the eeγ (μμγ) final state, we measure the Zγ production cross section for a photon with transverse energy ET > 7   GeV, separation between the photon and leptons Δ Rℓ γ > 0.7, and invariant mass of the di-lepton pair Mℓ ℓ > 30   GeV / c2, to be 4.96 ± 0.30 (stat . + syst .) ± 0.30 (lumi .)   pb, in agreement with the Standard Model prediction of 4.74 ± 0.22   pb. This is the most precise Zγ cross section measurement at a hadron collider. We set limits on anomalous trilinear Zγγ and ZZγ gauge boson couplings of - 0.085 < h30 γ < 0.084, - 0.0053 < h40 γ < 0.0054 and - 0.083 < h30 Z < 0.082, - 0.0053 < h40 Z < 0.0054 at the 95% C.L. for the form-factor scale Λ = 1.2   TeV.